2012
DOI: 10.1038/emboj.2012.95
|View full text |Cite|
|
Sign up to set email alerts
|

Large conformational changes in MutS during DNA scanning, mismatch recognition and repair signalling

Abstract: MutS protein recognizes mispaired bases in DNA and targets them for mismatch repair. Little is known about the transient conformations of MutS as it signals initiation of repair. We have used single-molecule fluorescence resonance energy transfer (FRET) measurements to report the conformational dynamics of MutS during this process. We find that the DNA-binding domains of MutS dynamically interconvert among multiple conformations when the protein is free and while it scans homoduplex DNA. Mismatch recognition r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
142
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(162 citation statements)
references
References 66 publications
16
142
1
Order By: Relevance
“…Despite the available crystal structures of MutS and MutS homologs bound to mispair-containing DNAs (2, 4, 18, 30), biochemical and genetic evidence suggests that crucial aspects of the function of MutS involve conformational states that have yet to be characterized at an atomic level (21,22,24,42,43). Here, we demonstrate the compatibility of PEG-coated gold labels on DNA with proteins and follow the effects of MutS conformational states and MutS/MutL association on DNA conformations.…”
Section: Discussionmentioning
confidence: 71%
“…Despite the available crystal structures of MutS and MutS homologs bound to mispair-containing DNAs (2, 4, 18, 30), biochemical and genetic evidence suggests that crucial aspects of the function of MutS involve conformational states that have yet to be characterized at an atomic level (21,22,24,42,43). Here, we demonstrate the compatibility of PEG-coated gold labels on DNA with proteins and follow the effects of MutS conformational states and MutS/MutL association on DNA conformations.…”
Section: Discussionmentioning
confidence: 71%
“…2) (Acharya et al 2003;Kolodner et al 2007). The mechanism that is most consistent with the data and the Brownian nature of molecular biology appears to be the molecular switch model (Gradia et al 1997(Gradia et al , 1999Fishel 1998Acharya et al 2003;Jeong et al 2011;Cho et al 2012;Gorman et al 2012;Qiu et al 2012;Spies 2013). Most, if not all, biochemical discrepancy can be traced to differences in the experimental conditions, an issue that persists today (Hall et al 2001;Drotschmann et al 2002;Tessmer et al 2008;Sass et al 2010;Tham et al 2013).…”
Section: Biochemical Activities Of the Mmr Proteinsmentioning
confidence: 63%
“…ATP exchange is a central function of all MSH proteins examined to date (Gradia et al 1997;Wilson et al 1999;Acharya et al 2003;Snowden et al 2004). ATP binding by the MSH dimer/heterodimer instigates a significant conformational transition (Gradia et al 1999;Wilson et al 1999;Acharya et al 2003;Qiu et al 2012), which results in an extremely stable (5-to 10-min lifetime) sliding clamp that freely diffuses along the DNA without ATP hydrolysis and in the absence of any stable backbone interactions ( Fig. 2A) (Cho et al 2012).…”
Section: Biochemical Activities Of the Mmr Proteinsmentioning
confidence: 99%
“…The structure of an ATP-bound MSH dimer has yet to be solved. However, numerous biochemical and single-molecule studies have demonstrated that mismatch recognition triggers ADP→ATP nucleotide exchange, which results in a conformational transition that converts the MSH dimer into an ATP-bound stable sliding clamp that disengages from the mismatch and freely diffuses on the adjacent dsDNA for 8-10 min (14)(15)(16)(17)(18)(19)(20)(21). The formation of an ATP-bound MSH sliding clamp is followed by recruitment of MutL homologs (MLH/PMS) (22,23).…”
mentioning
confidence: 99%